Detection of MRD may predict the outcome of patients with Philadelphia chromosome–positive ALL treated with tyrosine kinase inhibitors plus chemotherapy - Ravandi, Farhad; Jorgensen, Jeffrey L.; Thomas, Deborah A.; O'Brien, Susan; Garris, Rebecca; Faderl, Stefan; Huang, Xuelin; Wen, Sijin; Burger, Jan A.; Ferrajoli, Alessandra; Kebriaei, Partow; Champlin, Richard E.; et al. (Blood, 2013)
From 2001 to 2011, 122 patients with newly diagnosed Philadelphia chromosome–positive acute lymphoblastic leukemia were treated with chemotherapy + imatinib (n = 54) or + dasatinib (n = 68). One hundred fifteen (94%) achieved complete remission (CR) including 101 patients who achieved it with only 1 induction course and had at least 1 minimal residual disease (MRD) assessment; 25 patients underwent an allogeneic stem cell transplant in first CR and were excluded, leaving 76 patients as the subject of this report. MRD monitoring by multiparameter flow cytometry (MFC) and real-time quantitative polymerase chain reaction (PCR) was performed at the end of induction and at ∼3-month intervals thereafter. Median age was 54 years (range, 21-84 years). There was no difference in survival by achievement of at least a major molecular response (MMR; BCR-ABL/ABL < 0.1%) at CR (P = .22). Patients achieving MMR at 3, 6, 9, and 12 months had a better survival (P = .02, .04, .05, and .01, respectively). Negative MFC at CR did not predict for improved survival (P = .2). At 3 and 12 months, negative MRD by MFC was associated with improved survival (P = .04 and .001). MRD monitoring by PCR and MFC identifies patients who benefit from treatment intensification in first CR. •Detection of MRD by real-time quantitative PCR and flow cytometry is an important predictor of outcome in patients with Ph+ ALL.